Pengaruh Pendapatan Perkapita Dan CPI terhadap Konsumsi Masyarakat di Kota Banjarmasin - Sari, Novi Zulistri Anjung (PPJP ULM, 2018)
This research is conducted (1) To know how the effect of per capita income onpublic consumption in Banjarmasin ; (2) To know how CPI to public consumption InBanjarmasin. This researchh was conducted to measure the variables that influence theconsumption pattern of society by using macro economic concept. Economic variablesthat investigated are income Per Capita and CPI from 2000-2016 by using multiplelinear regression analysis. Based on hypothesis testing it can be seen that the influence of income of CPIconsumption in the city of Banjarmasin positively and significantly influence publicconsumption expenditure.